The taxation of couples - Patricia Apps; Ray Rees (Institute for the Study of Labor (IZA), 2007)
This paper is concerned with the question of how couples should be taxed. One reason for the importance of this issue is simply that the overwhelming majority of individuals live in households formed around couples, and so it could be argued that empirically, this is the single most important problem in personal income taxation. A second reason is that the economic theory of optimal taxation and tax reform, at least as it is presented in the mainstream literature, provides little guidance on this issue, resting as it does on models of the single person household. An old insight in the earlier public finance literature is that any discussion of the taxation of two-person households necessarily involves the recognition of the importance of household production. In this paper we try to show how a simple model of household production can be used to help the analysis of optimal taxation and tax reform, and to put the conventional wisdom, which says that it is optimal to tax women on a separate, lower tax schedule than men, on a firmer basis. What emerges clearly from the analysis is how centrally important the relationship between productivity in household production and female labour supply really is, and how little we know about it empirically.
Keywords: 330; Optimale Besteuerung; Familienbesteuerung; Haushaltsproduktion; Arbeitsangebot; Theorie